Bone marrow-derived mononuclear cells do not exert acute neuroprotection after stroke in spontaneously hypertensive rats - Minnerup, Jens; Wagner, Daniel-Christoph; Strecker, Jan-Kolja; Pösel, Claudia; Sevimli-Abdis, Sevgi; Schmidt, Antje; Schilling, Matthias; Boltze, Johannes; Diederich, Kai; Schäbitz, Wolf-Rüdiger (Frontiers in Cellular Neuroscience, 2014)
Bone marrow-derived mononuclear cells (BM-MNC) were shown to improve the outcome in animal stroke models and clinical pilot studies on BM-MNCs for stroke patients were already conducted. However, relevant aspects of preclinical evaluation, such as the use of animals with comorbidities and dose-response studies, were not thoroughly addressed so far. We therefore investigated different BM-MNC doses in the clinical meaningful stroke model of spontaneously hypertensive (SH) rats. Three hours after the onset of transient middle cerebral artery occlusion (MCAO) animals received either one of three syngeneic BM-MNC doses or placebo intravenously. The primary endpoint was the infarct size. Secondary endpoints included functional outcome, mortality, inflammatory processes, and the dose-response relationship. In contrast to previous studies which used healthy animals no beneficial effect of BM-MNCs was found. Infarct volumes, mortality, behavioral outcomes, and the extent of the inflammatory response to cerebral ischemia were comparable in all groups. In conclusion, we could not demonstrate that early BM-MNC treatment improves the outcome after stroke in SH rats. Whether BM-MNCs improve neurological recovery after delayed treatment initiation was not investigated in the present study, but our data indicates that this should be determined in co-morbid animal stroke models before moving to large-scale clinical studies. Future preclinical stroke studies on co-morbid animals should also include groups of healthy animals in order to determine whether negative results can be attributed to the comorbid condition.